The Analysis of Relationship Between Punctuation and Pronunciation Skills - Natasya Miranda Gihar; Rismayani Marpaung; Yani Lubis; Hanyan Zhu (JELT : Journal of English Education, Teaching and Literature, 2024)
Punctuation is one of the most important aspects of the English language. However, punctuation is often associated with writing ability alone, even though in fact punctuation also plays a big role in pronunciation ability. And this research is intended to discuss the relationship between punctuation and pronunciation ability. To find out whether they are related and what causes them to be related. This research was conducted using the interview method by asking participants' opinions regarding the relationship between punctuation and pronunciation skills. The author also uses qualitative descriptive research to provide a systematic and factual description of the topic under study. And the results of this research are expected to provide a more in-depth picture of punctuation marks in improving pronunciation abilities.